Patient Comprehension of Carpal Tunnel Surgery: An Investigation of Health Literacy. (March 2017) - Waryasz, Gregory R.; Gil, Joseph A.; Chiou, Daniel; Ramos, Paul; Schiller, Jonathan R.; DaSilva, Manuel F.
Background: Health literacy is the ability of a patient to understand their medical condition. The purpose of this investigation is to determine whether patients are able to obtain an elementary understanding of the fundamental principles of carpal tunnel release and the postoperative instructions after going through the process of informed consent and being provided an additional standardized postoperative instruction document. Our hypothesis is that patients will lack an understanding of these principles and, therefore, will be at risk for being noncompliant in their postoperative care.Methods: Fifty patients with a diagnosis of carpal tunnel surgery who elected to undergo carpal tunnel release alone were enrolled. A standardized education process was performed. Patients completed the questionnaire at their postoperative visit.Results: The average percentage of correct answers was 75.8% (8.34 out of 11 correct). Fisher exact test analysis demonstrated that patients with a lower education level were less likely to know how long it takes for their preoperative symptoms to resolve ( P = .0071), and they were less likely to correctly choose all of the important elements of postoperative care during the first week after surgery ( P = .022).Conclusions: Although we made efforts to help patients achieve health literacy in carpal tunnel surgery, we found that patients continued to lack comprehension of pertinent components of carpal tunnel surgery, particularly understanding the involved anatomy.